Behavioral Interventions in Tax Compliance : Evidence from Guatemala - Kettle, Stewart; Hernandez, Marco; Ruda, Simon; Sanders, Michael (World Bank, Washington, DC, 2016)
This paper presents results from a large (43,387) nationwide randomized controlled trial in Guatemala that used reminders to promote tax compliance. The trial varied the letter received by taxpayers (individuals and firms) who had failed to pay their income tax for the 2013 tax year. Taxpayers were randomly allocated to receive either no letter, the letter originally used by the Guatemalan Tax Authority, or four letter variants adapted using behavioral design. The study finds that although all letters increased the rate of declaration, only two of the letters were successful at increasing the rate of payment and the average amount paid per letter received. The best performing treatments were a deterrent message framing non-declaration as an intentional and deliberate choice, rather than oversight (designed to overcome status quo bias), and a social norms message that referred to the 64.5 percent of taxpayers that had already paid this tax (join the status quo). These two interventions increased the rate of payment as well as the average amount paid conditional on paying, overall more than tripling tax receipts. The paper estimates that if sent to all taxpayers in the sample, in 11 weeks the social norms letter would have generated additional tax revenues of approximately US$760,000, which is 36 times the cost of sending the letters. The effects are persistent and remain at 12 month follow up, suggesting the letters are effective in increasing revenue for the tax authority rather than just bringing tax receipts forward.